International Conference devoted to the 120th anniversary of deciphering the Orkhon-Yenisey script - Mizhit, Lyudmila S. (The New Research of Tuva, 2013)
On June 10-11, 2013 international conference "Turkic runics: language, history, culture” was held in Kyzyl devoted to the 120thanniversary of deciphering the Orkhon-Yenisey script. Article reviews the conference.
Keywords: conference-2013; Tuva; Orkhon-Yenisey script; Turkology; Philology; cultural studies